Incidence and Impact of Routine Inflammatory Parameters on Outcome after Transcatheter Aortic Valve Replacement. (15th April 2021) - Patsalis, Polykarpos C; Aweimer, Assem; Scharkowski, Henrik; Useini, Dritan; Haldenwang, Peter Lukas; Strauch, Justus Thomas; Canbay, Ali; Mügge, Andreas; Katsounas, Antonios
Abstract : Background . Previous research reported adverse clinical outcomes in association with systemic inflammation (SI) after transcatheter aortic valve replacement (TAVR). However, data characterizing the impact of SI, as reflected by postprocedural routine inflammatory parameters (pRIP), on clinical outcome of patients undergoing TAVR are sparse. Objectives . In light of this, the present work aimed to analyze incidence and clinical significance of pRIP after transapical (TA) and transfemoral (TF)-TAVR. Methods and Results . Data of 81 high-risk consecutive patients undergoing TAVR in our center from 2017 to 2018 were analyzed in a retrospective manner. 40 out of 81 patients (49, 4%) were treated via TF access (group A) and 41 patients via TA access (group B). Incidence, cause, and amplitude of pRIP were analyzed in relation to pre- and peri-interventional data. Assessment of outcomes was conducted according to the valve academic research consortium (VARC-2). Postprocedural C-reactive protein (pCRP) and leucocytes (pL) were significantly increased in patients undergoing TA-TAVR (group B) vs. TF-TAVR (group A; 12.1 ± 9.7 vs. 22.1 ± 7.9 mg/dl, p < 0.001 and 12.8 ± 4.0 vs. 14.2 ± 3.8/nl, p = 0.002); however, there was no significant difference regarding incidence of postprocedural fever (pF) ≥38.0°C (12.5% vs. 22%, p = 0.37). Furthermore, we observed a vast (though insignificant) trend towards a longer fever duration in group B vs. group A (9.9 ± 14.9 vs. 3.2 ± 5.9 hours, p = 0.06). Further analysis identified pCRP >30 mg/dl (hazard ratio (HR) 3.15, confidence interval (CI) 1.22–8.14, p = 0.018) and European System for Cardiac Operative Risk Evaluation (logistic EuroSCORE I (ES)) >20% (HR 2.95, CI 1.17–7.47, p = 0.02) as predictors of mortality; in this context, we also discovered a marginally significant trend for pL > 14/nl (HR 2.44, CI 0.97–6.14, p = 0.05). Multivariate analysis by use of the fisher`s exact test revealed a significant association between pCRP >30 mg/dl and ES >20% (p < 0.001). Conclusion . pRIP are significantly increased in patients undergoing TA-TAVR. pCRP >30 mg/dl, ES>20%, and pL > 14/nl are hallmark of adverse prognosis and require further investigation.